A note on the economics of philanthropy - Nathalie Monnet; Ugo Panizza (Graduate Institute of International and Development Studies, 2017)
This note starts with a short review of the economic literature on philanthropy. Next, it provides some estimates of philanthropic giving in advanced and middle-income economies and discusses how innovative financial instruments can leverage charitable giving. The note concludes with a discussion of the controversial aspects of philanthropic activities.
Keywords: D64; H21; H44; 330; Philanthropy; Taxation; Redistribution; Social welfare